Museum Epigenomics: Charting the Future by Unlocking the Past. (April 2020) - Hahn, Erin E.; Grealy, Alicia; Alexander, Marina; Holleley, Clare E.
Abstract : Epigenomic state preserved in museum specimens could be leveraged to provide unique insights into gene regulation trends associated with accelerating environmental change during the Anthropocene. We address the challenges facing museum epigenomics and propose a collaborative framework for researchers and curators to explore this new field.